PERAN OSIM DALAM MENINGKATKAN SIKAP KPEMIMPINAN SISWA DI MTsN 2 AGAM - Fauziyah Maulia; Bambang Trisno; Agus Salim (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Character education is an important component in education which aims to shape the character, morals and character of students. Character education does not only focus on developing academic knowledge, but also on developing values, ethics and good behavior. The main goal of character education is to help students become individuals who think critically, act with integrity, have empathy and have positive characteristics that diflerentiate them. So a forum is needed to be able to develop leadership attitudes possessed by students, namely through the role of OSIM. The role of OSIM (Intra Madrasa Student Organization) is an organization that exists at the madrasa levl in Indonesia. OSIM plays an important role in developing students in the madrasa environment. Observation findings show that students lack time management skills, lik to make noise, act impolitely and do not follow school policies. This shows that researchers want toinvestigate the function of OSIM In helping children develop their character. The aim of this research is regarding the role of OSIM in shaping the leadership character of students at MTsN 2 Agam so that they become complete human beings. Researchers conducted research in the from of qualitative descriptive research. Conclusions that can be drawn from research findings at MTsN 2 Agam regarding the contribution of OSIM in improving student leardership. The aim is that by participating in various events and activities at OSIM, students can develop their leadership skills and utilize the space to express the ideas and abilities that exist within the students.